Outcomes of STEMI patients with chronic kidney disease treated with percutaneous coronary intervention: the Malaysian National Cardiovascular Disease Database – Percutaneous Coronary Intervention (NCVD-PCI) registry data from 2007 to 2014 - Muhammad Dzafir Ismail; Maisarah Jalalonmuhali; Zaid Azhari; Jeevitha Mariapun; Zhen-Vin Lee; Imran Zainal Abidin; Wan Azman Wan Ahmad; Ahmad Syadi Mahmood Zuhdi; On behalf of NCVD-PCI investigators (BMC Cardiovascular Disorders, 2018)
Abstract Background Patients with renal impairment often left out from most major clinical trials assessing the optimal treatment for ST-elevation myocardial infarction (STEMI). Large body of evidence from various cardiovascular registries reflecting more ‘real-world’ experience might contribute to the knowledge on how best to treat this special cohort. We aim to analyze the outcomes of Malaysian STEMI patients with renal impairment treated with coronary angioplasty. Methods Utilizing the Malaysian National Cardiovascular Disease Database-Percutaneous Coronary Intervention (NCVD-PCI) registry data from 2007 to 2014, STEMI patients treated with percutaneous coronary intervention (PCI) were stratified into presence (GFR < 60 mls/min/1.73m2) or absence (GFR ≥ 60 mls/min/1.73m2) of chronic kidney disease (CKD). Patient’s demographics, extent of coronary artery disease, procedural data, discharge medications, short (in-hospital) and long (1 year) term outcomes were critically assessed. Results A total of 6563 patients were included in the final analysis. STEMI CKD cohort was predominantly male (80%) with mean age of 61.02 ± 9.95 years. They had higher cardiovascular risk factors namely diabetes mellitus (54.6%), hypertension (79.2%) and dyslipidemia (68.8%) in contrast to those without CKD. There were notably higher percentage of CKD patients presented with Killip class 3 and 4; 24.9 vs 8.7%. Thrombolytic therapy remained the most commonly instituted treatment regardless the status of kidney function. Furthermore, our STEMI CKD cohort also was more likely to receive less of evidence-based treatment upon discharge. In terms of outcomes, patients with CKD were more likely to develop in-hospital death (OR: 4.55, 95% CI 3.11–6.65), MACE (OR: 3.42, 95% CI 2.39–4.90) and vascular complications (OR: 1.88, 95% CI 0.95–3.7) compared to the non-CKD patients. The risk of death at 1-year post PCI in STEMI CKD patients was also reported to be high (HR: 3.79, 95% CI 2.84–5.07). Conclusion STEMI and CKD is a deadly combination, proven in our cohort, adding on to the current evidence in the literature. We noted that our STEMI CKD patients tend to be younger than the Caucasian with extremely high prevalence of diabetes mellitus. The poor outcome mainly driven by immediate or short term adverse events peri-procedural, therefore suggesting that more efficient treatment in this special group is imperative.